Evaluation of Salacca sumatrana as soil conservation crop in South Tapanuli, North Sumatra, Indonesia - YUSRIANI NASUTION (Society for Indonesian Biodiversity, 2019)
Abstract. Nasution Y, Rasyidin A, Yulnafatmawita, Saidi A. 2019. Evaluation of Salacca sumatrana as soil conservation crop in South Tapanuli, North Sumatra, Indonesia. Biodiversitas 20: 664-670. Salacca sumatrana Becc (snake fruit; or ‘Salak' in local name) is a profitable commodity. Morphologically, it is characterized by low, wide canopy that is potential intercept rainfall, while its roots are able to withstand soil erosion. This study is aimed to evaluate one variety of S. sumatrana named ‘salak sidimpuan